How Do Urban Environments Impact Walkability? An Analysis Using Multi-Source Data of Beijing - Changming Yu; Xinyu Wang; Ziao Zheng; Stephen Siu Yu Lau (Land)
Purpose: Recognizing that walkability is a fundamental element of sustainable urban development, this study focuses on the variables affecting walkability in the living environment and aims to provide insights into land use planning strategies that can contribute to carbon emission reduction. The research specifically examines how to create a pedestrian-friendly street environment in existing urban areas, where employment and residential functions are mixed and co-exist. Methodology: By using multi-source data, this research evaluates streets based on two binary characteristics: the occurrence of walking activity and the walking experience. Findings: The results reveal a strong relationship between walking opportunities and street usage frequency, with the road network being identified as the most influential factor. Additionally, the impact of walking experience was found to be more significant than that of walking opportunity. Contributions: First, the study developed a matrix of dependent variables for street usage frequency and walking experience, and an independent variable matrix for street environment factors. Second, the research created an analytical framework to examine factors influencing street use and experience across different travel needs.